La eficiencia de Ram Thai con Nueve Cuadrados de baile en el rendimiento físico y funciones cognitivas: un modelo para la escuela de personas mayores (The efficiency of Ram Thai with Nine Square dance on physical performance and cognitive functions: a model for elderly school) - Phanpheng, Yanyong; Pongkan, Preeyawan; Kusuma, I Dewa Made Aryananda Wijaya; Rohmansyah , Nur Azis; Wongkiew , Chawis; Laha , Warayot (Retos, 2024)
Los declives relacionados con la edad en la aptitud física relacionada con la salud y la función cognitiva pueden mitigarse mediante un programa de ejercicio de múltiples movimientos. Por lo tanto, el objetivo de este estudio fue determinar la eficacia de Ram Thai con nueve bailes cuadrados en el rendimiento físico y las funciones cognitivas en personas mayores. Los participantes fueron asignados al azar en un grupo experimental o de control. La evaluación cognitiva básica de Montreal (MoCA-B, versión tailandesa) se eligió de voluntarios seleccionados y se asignaron al azar en 2 grupos; Ram Thai con nueve bailes cuadrados (RTND:33) y ejercicio de caminata rápida (BWE:34) con una edad de 65.3±2.4 años, un índice de masa corporal (BMI) de 25.5±11.9 kg/m2. Los parámetros de rendimiento físico evaluados fueron los siguientes: prueba de rasguño de espalda (BST), prueba de estiramiento de silla (CSRT), prueba de levantamiento de silla (CST), prueba de curl de brazo de 30 segundos (ACT), prueba de caminata de 6 minutos (6-WT) y prueba de levantarse y andar cronometrado (TUG) se realizaron respectivamente. Nuestros resultados mostraron que los aspectos fisiológicos revelaron una reducción en el porcentaje de grasa corporal, mientras que se observó un aumento significativo en las puntuaciones de la prueba VO2max en ambos grupos (p≤.05). Además, hubo una mejora en la fuerza de las extremidades inferiores, como lo demuestran aumentos estadísticamente significativos en las puntuaciones para CST, 6-WT y TUG en comparación con los valores previos a la prueba (p≤.05). En cuanto al rendimiento de BST, el grupo RTND mostró resultados significativamente mejores en comparación con el grupo BWE (p≤.001). Además, descubrimos que los resultados significativamente superiores indican una mayor variabilidad en las puntuaciones de MoCA-B (24.11≈26.37) entre los participantes mayores en el grupo RTND (p≤.001). Los datos indican que RTND mejora eficazmente los aspectos fisiológicos, el control del rendimiento físico y la función cognitiva general en personas mayores con deterioro cognitivo leve (MCI).Palabras clave: rendimiento físico, función cognitiva, deterioro cognitivo leve, personas mayoresAbstract. Age-related declines in health-related physical fitness and cognitive function can be mitigated by a multi-movement exercise program. Therefore, the aim of this study was to determine the efficiency of Ram Thai with nine square dances on physical performance and cognitive functions in the elderly. Participants were randomly assignedinto an experimental or control group. The Montreal cognitive assessment-basic (MoCA-B, Thai version) were chosen from screened volunteers and randomly assigned into 2 groups; Ram Thai with nine square dances (RTND:33) and brisk walking exercise (BWE:34) aged 65.3±2.4 years old, body mass index (BMI) 25.5±11.9 kg/m2. The physical performance parameters assessed were as follows: Back-scratch test (BST), Chair sit and reach test (CSRT), Chair stand test (CST), 30-second arm curl test (ACT), 6-minute walk test (6-WT) and timed up and go test (TUG) were conducted respectively. Our results showed the physiological revealed a reduction in body fat percentage, while significant increase in VO2max test scores observed in both groups (p≤.05). Additionally, there was an improved lower limb strength, as evidenced by statistically significant increases in scores for the CST, 6-WT, and TUG compared to pretest values (p≤.05). In terms of BST performance, the RTND group showed significantly better results compared to the BWE group (p≤.001). Moreover, we discovered that significantly superior results indicate increased variability in MoCA-B scores (24.11≈26.37) among elderly participants in the RTND group (p≤.001). The data indicates that RTND effectively enhances physiological aspects, physical performance control, and overall cognitive function in elderly individuals with mild cognitive impairment (MCI).Keywords: physical performance, cognitive function, mild cognitive impairment, elderlyAbstract. Age-related declines in health-related physical fitness and cognitive function can be mitigated by a multi-movement exercise program. Therefore, the aim of this study was to determine the efficiency of Ram Thai with nine square dances on physical performance and cognitive functions in the elderly. Participants were randomly assignedinto an experimental or control group. The Montreal cognitive assessment-basic (MoCA-B, Thai version) were chosen from screened volunteers and randomly assigned into 2 groups; Ram Thai with nine square dances (RTND:33) and brisk walking exercise (BWE:34) aged 65.3±2.4 years old, body mass index (BMI) 25.5±11.9 kg/m2. The physical performance parameters assessed were as follows: Back-scratch test (BST), Chair sit and reach test (CSRT), Chair stand test (CST), 30-second arm curl test (ACT), 6-minute walk test (6-WT) and timed up and go test (TUG) were conducted respectively. Our results showed the physiological revealed a reduction in body fat percentage, while significant increase in VO2max test scores observed in both groups (p≤.05). Additionally, there was an improved lower limb strength, as evidenced by statistically significant increases in scores for the CST, 6-WT, and TUG compared to pretest values (p≤.05). In terms of BST performance, the RTND group showed significantly better results compared to the BWE group (p≤.001). Moreover, we discovered that significantly superior results indicate increased variability in MoCA-B scores (24.11≈26.37) among elderly participants in the RTND group (p≤.001). The data indicates that RTND effectively enhances physiological aspects, physical performance control, and overall cognitive function in elderly individuals with mild cognitive impairment (MCI).Keywords: physical performance, cognitive function, mild cognitive impairment, elderly